The Effect of Conscious Awareness on Psychological Well-Being: Mediating Role of Boredom in Leisure Time - Işık, Utku; Karakullukçu, Ömür Fatih; Güngörmüş, Hamdi Alper (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2020)
This study aimed to investigate the effectiveness and mediation of boredom in leisure time in the effect of conscious awareness on psychological well-being among secondary school students. The research group of the study consisted of 192 students with an average age of Mage = 16.32 +/- 0.91 who studied at secondary education institutions in Manisa. Participants answered the "Psychological Well-Being Scale," "Conscious Awareness Scale," and "Boredom in Leisure Scale." In the study, the effect of conscious awareness on psychological well-being was tested with Simple Linear Regression Analysis. Baron and Kenny's method was used as the mediating effect of boredom. To determine how effective the mediated role, bootstrap confidence interval values were used. According to the analyzes, it was seen that conscious awareness had a significant effect on psychological well-being (β =, 4204; F(1,190) = 15,507; p <0.05). Both the competence sub-dimension and the motivation sub-dimension of the Leisure Boredom Scale were included as a mediator variable, the power of the relationship between conscious awareness and psychological well-being was decreased. In other words, mediator variables decreased the power of the effect. Bootstrap confidence intervals were checked to determine whether the indirect effect was significant. It was seen that bootstrap confidence intervals were below and above zero in both sub-dimensions and sub-dimensions of boredom scale have a partial mediating effect. As a result, conscious awareness positively affects psychological well-being. However, among students suffering from boredom in their leisure time, this effect tends to decrease. There was a decrease in the participants' psychological well-being, who were bored in their leisure time. Although conscious awareness effect on psychological well-being, the power of the effect decreases.